Innovation rooted in desing strategies based on users tastes (2021)
The need fin innoration is a challenge that oi:ganiationifi ice ercq day and indushial design has become alundamental component to address it. 7.bis /i-nk innoration miented design shwtegies arc applying ethnographic methodologies that offer a better underftandiligof the people's behavior and the culture in oakr to create IMP products and SCI•I(eS. This applied/1011 Lc highlighted in this article developed by the Research Group of Ithrironment and Design.